Innovative Learning Media in the Era of Society 5.0: The Use of Wordwall Based on Local Wisdom of Batik Trusmi - Yusriyani Mulyawati; Fityah Nabilah Nabilah; Aan Anisah; Rusdiyana Rusdiyana (Universitas Negeri Padang, 2025)
This study was designed to measure the level of learning outcomes of students at MAN 1 Cirebon in economics subjects using Wordwall based on local wisdom Batik Trusmi, using the research and development (R&D) method with the ADDIE model quantitative approach. The research sample was the control class (X.10) of 33 students and the experiment class (X.12) of 29 students, taken using a purposive sampling technique. Data were obtained from observations, interviews, and questionnaires. Data analysis includes product validity testing by media experts, material experts, and practitioners, as well as calculation of N-Gain scores through pretests and posttests, practicality tests, and the Mann-Whitney U Test. The validity test results showed that the average score of the three experts was 91%. The N-Gain score of the control class is 0.62 (moderate improvement) and the experiment class is 0.75 (high improvement), p-value 0.046 (<0.05) there is a significant difference between the two classes, and the results of the practicality test of the control class are 71% (practical) and the experiment class is 85% (efficient). Based on the study results, it is concluded that Wordwall teaching media is more effective for improving student learning outcomes than conventional teaching media.